Physicians' Persistence and Its Implications for Their Response to Promotion of Prescription Drugs - Janakiraman, Ramkumar; Dutta, Shantanu; Sismeiro, Catarina; Stern, Philip (Management Science, 2008)
Motivated by the medical literature findings that physicians are inertial, we seek to understand (1) whether physicians exhibit structural persistence in drug choice (structural persistence occurs when the drug chosen for a patient depends structurally on the drug previously prescribed by the physician to other patients) and (2) whether persistence, if present, is a physician-specific characteristic or a physician state that can change over time. We further explore the role of promotional tools on persistence and drug choice, and we investigate whether physicians who exhibit persistence respond differently to three forms of sales promotion: one-to-one meetings (detailing), out-of-office meetings, and symposium meetings. Our results show significant levels of physician persistence in drug choice. We find that persistence is mostly a cross-sectional physician feature. Nonpersistent physicians appear to be responsive to detailing and symposium meetings, whereas persistent physicians seem to be responsive only to symposium meetings. Out-of-office meetings, such as golf or lunch, have no effect on physicians' drug choice. We also find that (1) older physicians and those who work in smaller practices are more likely to be persistent and (2) physicians who are more willing to receive sales force representatives have a lower likelihood of being persistent. Finally, we discuss implications for public policy from our rich set of results.